Estimated direct medical cost of orthopaedic trauma surgery in Saudi Arabia: a single-centre retrospective cost analysis - Waleed Albishi; Amjad Albaroudi; Abdullah Addar; Hisham Alsanawi; Abdulrahman Alaseem (Journal of Orthopaedic Surgery and Research)
Abstract Background Physical trauma is a significant contributor to morbidity and mortality worldwide. In Saudi Arabia, RTAs are the leading cause of injuries, with fractures being a critical aspect of trauma care. To address this prevalent healthcare burden, a detailed analysis of the costs associated with surgical interventions to optimize resource allocation and improve healthcare planning is crucial. Method This retrospective cost analysis was conducted at King Saud University Medical City between January 2016 and March 2022. A total of 2689 orthopaedic trauma surgeries were analysed. The cost data were converted to US dollars (1 USD = 3.75 SR). Statistical analysis was conducted via SPSS, with comparisons of costs by sex, age group, procedure type, and other relevant factors. Results The total cost of trauma surgeries over the study period was $8,548,749.90. The most common procedure was ORIF, which was performed 1415 times, accounting for $5,660,000.00 of the total cost. Males represented 65.7% of the patients, incurring $5,647,976.44 in expenses. Patients under the age of 21 had the highest number of cases by age (43.5%), and the total cost was $3,276,293.44. Scheduled surgeries had higher average costs than emergent procedures did, and lower extremity surgeries accounted for more cases but had lower average costs than upper extremity surgeries did. Conclusion The cost of orthopaedic trauma care is significantly influenced by factors such as procedure type, age, and sex. When certain cost patterns are identified and analysed, an approach toward cost effectiveness while maintaining high-quality healthcare delivery can be achieved. Projected trends show an increase in the number of cases by 2030, indicating increased costs. Future studies should consider additional factors, such as rehabilitation costs, and explore cost-saving opportunities in surgical interventions.